Assessment of Circulating Tumor Cells in Colorectal Cancer as an Adjunctive Non-invasive Diagnostic Method - Saskia Aziza Nursyirwan; Murdani Abdullah; Andri Sanityoso Sulaiman; Ikhwan Rinaldi; Dadang Makmun; Marcellus Simadibrata; Dimas Ramadhian Noor; Agustinus Wiraatmadja; Wifanto Saditya Jeo; Nur Rahadiani; Diah Rini Handjari; Hamzah Shatri (Acta Medica Indonesiana, 2024)
Background: Colorectal cancer (CRC) is a significant contributor to cancer-related morbidity and mortality. Biopsy remains the gold standard for CRC diagnosis, but invasive testing may not be preferred as an initial diagnostic procedure. Therefore, alternative non-invasive approaches are needed. Circulating tumor cells (CTC) present in the bloodstream have great potential as a non-invasive diagnostic marker for CRC patients. This study aimed to assess the diagnostic potential of CTC in CRC as an adjunctive diagnostic method using a subjective manual identification method and laser capture microdissection at 40x magnification. Methods: A cross-sectional study was conducted on adult patients suspected to have CRC at Dr. Cipto Mangunkusumo National General Hospital, Jakarta, between November 2020 and March 2021. CTC analysis was performed using the negative selection immunomagnetic method with Easysep™ and the CD44 mesenchymal tumor marker. The identification and quantification of CTC were conducted manually and subjectively, with three repetitions of cell counting per field of view at 40x magnification. Results: Of 80 subjects, 77.5% were diagnosed with CRC, while 7.5% and 15% exhibited adenomatous polyps and inflammatory/hyperplastic polyps, respectively. The diagnostic analysis of CTC for detecting CRC (compared to polyps) using a CTC cutoff point of >1.5 cells/mL suggested sensitivity, specificity, and positive predictive value (PPV) of 50%, 88.89%, and 93.94%. Additionally, the negative predictive value (NPV), as well as the positive and negative likelihood ratio (PLR and NLR) were 34.04%, 4.5, and 0.56, respectively. The subjective manual identification and quantification of CTC were performed at 40x magnification using laser capture microdissection. Conclusion: This study assessed the diagnostic potential of CTC examination in CRC as an adjunctive diagnostic method using the subjective manual identification method and laser capture microdissection at 40x magnification. Despite the limitations associated with subjective cell counting, the results showed 50% sensitivity and 88.89% specificity in diagnosing CRC. Further studies are needed to optimize the manual identification process and validate the clinical utility of CTC analysis in CRC patients.